Lumped elements for RF and microwave circuits - Bahl, I. J. (Boston : Artech House, 2003)
Due to the unprecedented growth in wireless applications over the past decade, development of low-cost solutions for RF and microwave communication systems has become of great importance. This practical new book is the first comprehensive treatment of lumped elements, which are playing a critical role in the development of the circuits that make these cost-effective systems possible. The books offers you an in-depth understanding of the different types of RF and microwave circuit elements, including inductors, capacitors, resistors, transformers, via holes, airbridges, and crossovers.
List of Acronyms 195 -- About the Authors 203 -- Index 205.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Lumped elements (Electronics); Microwave integrated circuits; Radio frequency integrated circuits; Passive components; Constantes localisées (Électronique); Circuits intégrés pour micro-ondes.; Circuits intégrés à radiofréquence.; Composants passifs; TECHNOLOGY & ENGINEERING -- Mining; Lumped elements (Electronics); Microwave integrated circuits; Passive components; Radio frequency integrated circuits; Andre fag (naturvidenskab og teknik) -- Andre fag